Utilization of Juice Beta vulgaris. L as an Alternative Reagent for Examination of Worm Eggs Ascaris lumbricoides - Sri Kartini; Eni Angelia (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Riau, 2021)
Beetroot (Beta vulgaris) is a type of red tuber plant originating from North America that has many benefits, one of which is to overcome anemia. Beetroot (Beta vulgaris) is also acidic containing carotenoids that produce orange-red pigments. Eosin 2% is a dye used in the examination of worm Ascaris Lumbricoidess eggs which have orange-red color. The purpose of this study was to determine the concentration of a variety of beet juice (Beta vulgaris) which optimally can color the eggs of worms. The study was carried out experimentally with variations in the concentration of the ratio of beet juice with distilled water (1, 1: 1, 1: 2, 1: 3, 1: 4, 1: 5). After the research was conducted, the results showed that the concentration of beet juice (Beta vulgaris) and aquadest (1: 1) comparison could be used as an alternative to the 2% Eosin reagent for coloring worm eggs. This study it can be concluded that beetroot (Beta vulgaris) can be used to coloring the eggs of Soil worms transmitted helminths.